Redesign Perpustakaan Daerah Di Ambon - Miru, Anissa Agustina; Sari, Sriti Mayang (Intra, 2014)
Reading habit become more unpopular over time. It makes people become accustomed to browse their reference in the internet instead of looking for that in the books. People’s perspectives toward local library also affecting the existence of local library itself. Library are interpreted as a place with stacks of books which exist in a intrusive environment. This is also happened at Archive and Library Bureau of Moluccas. This library don’t have supportive facilities such as WiFi, photocopy machine and self reading spots for visitors. This prompted the author to re-design the library by adding some supporting facilities which are not yet available in this library. The author applying The Simple Flashy concept to this additional development. The concept using natural lighting as the main lighting source, applying dynamic layout, geometric formation and also Moluccas traditional icon as local identity of this library. This design are created with expectation to attract people to come to this library.